A checklist of the genus Scopula (Lepidoptera: Geometridae) including description of a new species and three newly recorded species from Korea - Choi, Sei-Woong; Kim, Sung-Soo (Zootaxa, 2016)
We present a checklist comprising 39 species of the genus Scopula (Geometridae, Sterrhinae) from Korea by adding four new records. One species Scopula paraconfusa Kim & Choi spec. nov. is described as new and three species S. butleri, S. disclusaria and S. hypochra are recorded to the Korean fauna for the first time. We provided the diagnosis for four species and male and female genitalia, if available.